Test For Antibacterial Activity Of Green Bean Extract (Vigna Radiata L.) Against Bacteria Escherichia Coli Using Well Diffusion Method - Rizky Amalia Eka Agustin (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2023)
Background: Mung beans (Vigna radiata L.) bioactive components that known antibacterial but for their benefits not widely known. This plant includes VIMA 5 mung bean type which the most common variates. Bacteria digestive tract infections Escherichia coliPurpose: to determine antibacterial activity of mung bean extract against bacteria that commonly infect digestive tract,namely Escherichia coli.Methods: Design of this research experimental laboratory using sokhletasi method with ethanol solvent. Sample used ethanol extract mung bean (Vigna radiata L.) concentration dilutions of 10%, 20%, 30% 40%. The positive control used chloramphenicol and negative control DMSO. Inhibition test using the well diffusion method with a diameter of 6 mm. Mung bean compounds contain bioactive components such as flavonoids, tannins, saponins and triterpenoids.Results: The test results show that mung bean seeds have antibacterial activity against Escherichia coli bacteria characterized by the presence of inhibition zones obtained on average for 10% concentration (11.04 mm), 20% concentration (12.04 mm), 30% concentration (12.83 mm), and 40% concentration (13.88 mm) where the whole is classified in the strong category.Conclusions: It can be concluded that the ethanol extract of mung bean seeds (Vigna Radiata L) has antibacterial activity.